Symplectic and hyperkähler implosion - Dancer, A; Kirwan, F; Doran, B; Swann, A (Birkhäuser, Cham, 2014)
We review the quiver descriptions of symplectic and hyperkähler implosion in the case of SU(n) actions. We give quiver descriptions of symplectic implosion for other classical groups, and discuss some of the issues involved in obtaining a similar description for hyperkähler implosion.